An empirical analysis of Value at Risk and Expected Shortfall in CDS and Equity markets - Chen, Hsiao-Ling (2016)
In this study, I investigate the risk of holding credit default swaps (CDS) of 98 most liquid firms in CDX investment grade index compare the Value at Risk (VaR) and Expected Shortfall (ES) of a CDS position to the VaR and ES of holding the equity of respective firms over a sample period from October 2004 to December 2015 in the U.S.. Our finding confirms that the risk of trading a CDS position is correlated with the risk of trading a respective firm’s equity measured by VaR and ES. Also, seemingly unrelated regression suggest that firm-specific variables contribute more in the risk discovery of CDS and equity market than market and Macro variables.